# math

posted by .

solve using substitution
4x + 3y= -3
2x + y = -1

• math -

When we look at the second equation, we can transfer the term 2x to the other side of the equality. We get that:

2x+y = -1
<=> y = -1-2x

when we replace the y in the first equation by the value we just calculated, we get that:

4x + 3y= -3
<=> 4x + 3(-1-2x)=-3
<=> 4x - 3 -6x = -3
<=> -2x=0
<=> x=0

So, we find that x=0. When we replace this value for x in the equation we earlier found for y, we get that:

y=-1-(2*0)=-1

So, we find that x=0 and y=-1

• math -

thanxz

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### Math

how do you solve this system? I'm using substitution.. y=3x+4 y=-x^2 First I combined it: -x^2=3x+4 I don't know how to solve it now..
3. ### math

solve each system of equations by substitution. y=3x-9 please help explain how to solve this using substitution.
4. ### algebra

i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of equations …
5. ### Calculus 2

Evalute the integral of x/(x^2+4)dx using u-substitution and then trigonometric substitution. I did this and got (1/2)ln(x^2+4)+C using u-substitution and x^2+4+C using trigonometric substitution. What did I do wrong?
6. ### math/ elimination& substitution

how do i solve this? using elimination or substitution?
7. ### Math

Solve using substitution 3x - 9y = 3 6x - 3y = -24 Solve using elimination y - 1/2x = 6 2x + 6y = 19
8. ### Math help

Solve using substitution 3x - 9y = 3 6x - 3y = -24 Solve using elimination y - 1/2x = 6 2x + 6y = 19